2020
DOI: 10.1111/ijfs.14879
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of phenolics, antioxidant and antiproliferative activity of sweet corn (Zea mays L.) during kernel maturation

Abstract: Phenolic profiles and gene expression pattern in their synthetic pathway, total antioxidant activities and antiproliferative activities in two genotypes of sweet corn (YT16 and YT28) during kernel maturation were analysed. Results showed that increasing trends of phenolics and flavonoids in the two genotypes of kernels from 10 to 30 days after pollination (DAP). Gallic acid, chlorogenic acid, p-coumaric acid and ferulic acid were identified and quantified as the main phenolic compounds in both genotypes of ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Chlorogenic acid, 3,4-dihydroxybenzoic acid and ferulic acid were identified as the main phenolic acids in the tested baby corn samples. Our results are well in accordance with data reported for sweet corn genotypes [49] as well as with literature data reporting that p-coumaric acid and ferulic acid were commonly identified in cereals [50][51][52]. Additionally, it had been reported that quercetin, kaempferol, vanillic, caffeic, and gallic acid were present [53,54].…”
Section: Phenolic Compound Content the Antioxidant Capacity And The C...supporting
confidence: 93%
“…Chlorogenic acid, 3,4-dihydroxybenzoic acid and ferulic acid were identified as the main phenolic acids in the tested baby corn samples. Our results are well in accordance with data reported for sweet corn genotypes [49] as well as with literature data reporting that p-coumaric acid and ferulic acid were commonly identified in cereals [50][51][52]. Additionally, it had been reported that quercetin, kaempferol, vanillic, caffeic, and gallic acid were present [53,54].…”
Section: Phenolic Compound Content the Antioxidant Capacity And The C...supporting
confidence: 93%
“…Nurraihana has used LC‐TOF/MS system to separate and identified 26 different phenolics in dry and mature corn silk, including flavone, flavone glycosides, flavonols, and isoflavone (Nurraihana, Wan Rosli, Sabreena, & Norfarizan‐Hanoon, 2018). According to previous data, the main phenolics in sweet corns were gallic acid, chlorogenic acid, p ‐coumaric acid, and ferulic acid and quercetin was only detected in corn silk compared with other part of corn (Hu, Liu, Yu, Li, Qi, Li, et al, 2021). Quercetin is a member of the flavonoid family and one of the main naturally occurring flavonol that has a long history of consumption as part of the normal human diet (Harwood, Danielewska‐Nikiel, Borzelleca, Flamm, Williams, & Lines, 2007).…”
Section: Resultsmentioning
confidence: 90%
“…Nurraihana has used LC-TOF/ MS system to separate and identified 26 different phenolics in dry and mature corn silk, including flavone, flavone glycosides, flavonols, and isoflavone (Nurraihana, Wan Rosli, Sabreena, & Norfarizan-Hanoon, 2018). According to previous data, the main phenolics in sweet corns were gallic acid, chlorogenic acid, p-coumaric acid, and ferulic acid and quercetin was only detected in corn silk compared with other part of corn (Hu, Liu, Yu, Li, Qi, Li, et al, 2021).…”
Section: Effect Of Drying Methods On Phenolic Profile In Mcsmentioning
confidence: 99%
“…Phenolic compounds are known to be more responsive to environmental factors than carotenoids (Zaynab et al, 2018). The degree of ripeness of the harvesting season would also be another factor to be considered, since different ripening stages may imply different phytochemical concentrations, including the content of carotenoids would be more affected than that of phenolic compounds (Hu et al, 2021). Nevertheless, there is no consensus on which factors would specifically affect the content of total carotenoids and total phenolics in different maize crops since there is a wide variety of species (Lopez-Martinez & Garcia, 2015).…”
Section: Resultsmentioning
confidence: 99%